Design and Implementation of NYSC Orientation Posting scheme in Nigeria - Sunday Olowookere, A; Oluwafemi Ayangbekun, J; Babatunde Oluwasola, S (International Journal of Computer Sciences and Engineering, 2019)
NYSC Posting Information system is designed to overcome the problems encountered with the existing system in terms of insecurity, data redundancy, Information time management and data protection, misplacement and mismanagement of files etc. The new system is designed in such a way that information about each corps member is effectively managed within the database for easy retrieval of information. The Top-down design approach model was used in the course of this research and data collected were implemented using Visual Basic 6 for the front end design and Microsoft Access for the Back end.